2018
DOI: 10.1080/01419870.2018.1533645
|View full text |Cite
|
Sign up to set email alerts
|

Bound between care and control: Institutional contradictions and daily practices of healthcare for migrants in an irregular situation in Italy

Abstract: The inclusiveness of the Italian framework on migrants' healthcare is indisputable "on the book". However, we might wonder how access takes shape at the front-line of the healthcare system in an increasingly hostile institutional and discursive environment. By focusing on Italian migration and healthcare policies and of health workers' practices in their encounters with migrants in irregular situation, this contribution analyses how institutional tensions are dealt with by -and simultaneously shape -workers' n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
(11 reference statements)
0
10
0
3
Order By: Relevance
“…A literatura internacional sobre o acesso de migrantes a sistemas nacionais de saúde evidencia situações diversas das que ocorrem no Brasil. Perna (2018) estudou como profissionais de saúde lidam com tensões institucionais em ambientes hostis para migrantes ilegais na Itália, refletindo as contradições entre uma lógica médico-humanitária e outra orientada pelo controle focando na migração e gastos em saúde. Chatzimpyros et al (2021) estudaram as representações sociais de provisão de saúde para pacientes imigrantes no sistema de saúde grego.…”
Section: Acesso E Universalidade Na Assistência à Saúde De Migrantesunclassified
See 1 more Smart Citation
“…A literatura internacional sobre o acesso de migrantes a sistemas nacionais de saúde evidencia situações diversas das que ocorrem no Brasil. Perna (2018) estudou como profissionais de saúde lidam com tensões institucionais em ambientes hostis para migrantes ilegais na Itália, refletindo as contradições entre uma lógica médico-humanitária e outra orientada pelo controle focando na migração e gastos em saúde. Chatzimpyros et al (2021) estudaram as representações sociais de provisão de saúde para pacientes imigrantes no sistema de saúde grego.…”
Section: Acesso E Universalidade Na Assistência à Saúde De Migrantesunclassified
“…Foram realizadas dez entrevistas em profundidade com profissionais que atuam em Universidad de Varsovia, Centro de Estudios Americanos diversos níveis de cuidado: 2 médicos(as), 4 enfermeiros(as), 1 nutricionista, 1 fonoaudiólogo (a), 1 assistente social e 1 técnico de nível superior. Não identificamos as nacionalidades citadas nas entrevistas para evitar reduzir os migrantes e suas biografias a marcadores étnicos ou nacionais que reforçam estereótipos e discriminações (Perna, 2018).…”
Section: Acesso E Universalidade Na Assistência à Saúde De Migrantesunclassified
“…In a context of economic crisis and austerity policies, the PP raised the reform's profile and claimed credit for it, believing that framing healthcare as a right linked to national membership and contribution to the social security system while scapegoating 'illegal and foreign abusers' would secure it support from conservative and antiimmigration voters. Accordingly, retrenchment discourse and policies publicly and openly targeted MIS, a prototype of 'welfare undeservingness' (Willen 2012;Perna 2019;Reeskens & van der Meer 2019), particularly at times of economic and migration crises. In doing so, it targeted a politically weak group, as MIS are excluded from any political rights, lacking any power to impose sanctions on the government.…”
Section: Symbolic Politics Converging Outputs and The Embeddedness Omentioning
confidence: 99%
“…It has been shown that policies of internal control encounter both support and resistance on the part of other local residents, the wider public, specific interest groups and civil society organisations, as well as individual professionals, civil servants and local government officials (Broeders and Engbersen 2007;Ellermann 2006;Guiraudon and Lahav 2000;Van der Leun 2006). Coinciding and conflicting interests can even be present simultaneously within the same institution, and a lot depends on individual motivations and perceptions (Perna 2018). Particularly where rigorous exclusion would create significant costs or contradictions, however, migrant irregularity is often more or less routinely accommodated within existing organisational structures and institutional logics (Schweitzer 2018b).…”
Section: A 'Hostile Environment' For Just One Category Of Residents?mentioning
confidence: 99%